Extraction of live leech from nasal cavity: an interesting case report from a rural area hospital (Bangladesh Journal of Otorhinolaryngology, 2012)
Introduction: Leeches are blood sucking invertebrate parasites. They are endemic in tropical regions like Asia, Africa and Mediterranean countries with different colors and sizes. Entry into human body is through drinking polluted water. These inhabit mucosa of nose, nasopharynx, oropharynx, tonsils, esophagus but rarely larynx.Case report: Here we report a case of live leech in the left nasal cavity in a 40-year-old male that caused symptoms of watery discharge and occasional epistaxis from left nostril along with headache. Habitual drinking of water from a natural source of water was assumed as the cause of leech infestation. The leech was extracted finally from oropharynx, with great effort as it continuously changed its locations.Conclusion: Leech infestation must be kept as differential diagnosis for various foreign bodies in the respiratory tract causing, unusual respiratory distress and epistaxis, especially in rural area people, where drinking water from natural sources of water is a regular habit. DOI: http://dx.doi.org/10.3329/bjo.v18i2.12027 Bangladesh J Otorhinolaryngol 2012; 18(2): 222-224